In the sea slug Melibe leonina the posterior nerves communicate stomach distention to inhibit feeding and modify oral hood movements - Lee, Colin Anthony; Watson, Winsor Hays (Frontiers in Physiology, 2022)
The sea slug Melibe leonina is an excellent model system for the study of the neural basis of satiation, and previous studies have demonstrated that stomach distention attenuates feeding. Here we expanded on this work by examining the pathway communicating stomach distention to the central nervous system and the effects of distention on motor output. We found that the posterior nerves (PN), which extend posteriorly from the buccal ganglia and innervate the stomach, communicate stomach distention in Melibe. PN lesions led to increased feeding duration and food consumption, and PN activity increased in response to stomach distention. Additionally, the percentage of incomplete feeding movements increased with satiation, and PN stimulation had a similar impact in the nerves that innervate the oral hood. These incomplete movements may be functionally similar to the egestive, food rejecting motions seen in other gastropods and enable Melibe to remain responsive to food, yet adjust their behavior as they become satiated. Such flexibility would not be possible if the entire feeding network were inhibited.